Talempong Minangkabau - Hanefi; Hermawan, Deni 1959-.; Universitas Pendidikan Indonesia. Pusat Penelitian dan Pengembangan Seni Tradisional (Bandung P4ST UPI, 2004)
On Minangkabau traditional music and dance from Sumatera Barat Province.
buku 1. [without special title] -- buku 2. Metodologi pengajaran seni talempong dan tari piring Minangkabau.
Keywords: Music -- Instruction and study -- Indonesia -- Sumatera Barat -- Outlines, syllabi, etc; Music -- Indonesia -- Sumatera Barat -- Analysis, appreciation; Minangkabau (Indonesian people) -- Indonesia -- Sumatera Barat -- Music -- Analysis, appreciation